System‐failing creativity in health care - Stijn Horck; Rachel E. Gifford; Bram P. I. Fleuren; Cheryl Rathert; Tracy H. Porter; Afshan Rauf; Yuna S. H. Lee (Learning Health Systems)
Abstract Introduction Health care professionals often generate novel solutions to solve problems during day‐to‐day patient care. However, less is known about generating novel and useful (i.e., creative) ideas in the face of health care system failure. System failures are high‐impact and increasingly frequent events in health care organizations, and front‐line professionals may have uniquely valuable expertise to address such occurrences. Methods Our interdisciplinary team, blending expertise in health care management, economics, psychology, and clinical practice, reviewed the literature on creativity and system failures in health care to generate a conceptual model that describes this process. Drawing on appraisal theory, we iteratively refined the model by integrating various theories with key concepts of system failures, creativity, and health care worker's well‐being. Results The SFC model provides a conceptualization of creativity from front‐line care professionals as it emerges in situations of failure or crisis. It describes the pathways by which professionals respond proactively to a systems failure with creative ideas to effectively address the situation and affect these workers' well‐being. Conclusions Our conceptual model guides health care managers and leaders to use managerial practices to shape their systems and support creativity, especially when facing system failures. It introduces a framework for examining system‐failing creativity (SFC) and general creativity, aiming to improve health care quality, health care workers' well‐being, and organizational outcomes.